2020
DOI: 10.1097/brs.0000000000003678
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Development of Urinary Retention Following Posterior Lumbar Spinal Fusion: Special Attention to the Use of Glycopyrrolate in Anesthesia Reversal

Abstract: Study Design. The study is designed as a retrospective cohort study. Objective. The aim of this study was to identify modifiable and nonmodifiable risk factors of postoperative urinary retention in spine surgery patients. Summary of Background Data. Postoperative urinary retention is a common complication in patients undergoing operative procedures requiring anesthesia. Current studies have shown significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…10 POUR is a common postoperative complication of anesthesia and surgery, and has reported incidences of 5% to 70%. 17 Sometimes, POUR continues for 4 to 6 weeks. 18 Numerous factors affect the incidence of POUR, including the age and sex of the patient, the type of surgery performed, the comorbidities present, the drugs administered, the intravenous fluids administered, the duration of surgery, and various anesthesiarelated parameters.…”
Section: Discussionmentioning
confidence: 99%
“…10 POUR is a common postoperative complication of anesthesia and surgery, and has reported incidences of 5% to 70%. 17 Sometimes, POUR continues for 4 to 6 weeks. 18 Numerous factors affect the incidence of POUR, including the age and sex of the patient, the type of surgery performed, the comorbidities present, the drugs administered, the intravenous fluids administered, the duration of surgery, and various anesthesiarelated parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal anesthesia does not influence the functions of the bladder sphincter muscle. Common causes of urinary retention include paralysis of the bladder sphincter and insensitivity to the micturition reflex caused by single spinal anesthesia, reflex spasms of the urethral sphincter caused by incision pain after perineum surgery, changes in micturition posture after surgery, excessive fluid replacement, and mental and psychological factors ( 25 , 26 ). Other studies have shown that factors that influence urinary retention after spinal anesthesia include the operation time and local anesthetic dosage ( 27 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 We also observed a statistically significant difference in the mean age of patients with and without POUR, with the AE being more prevalent in a relatively older population. 1,5,13,[15][16][17] Although both these observations were initially attributed to the higher prevalence of BPH in both these patient groups (older age and male gender), more recent studies have demonstrated a significant association between POUR and both these parameters, irrespective of the confounding variable. [22][23][24][25] Based on the available evidence, we were unable to clearly identify any cut-off age limit beyond which the need for prophylactic measures against POUR could be advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Included studies are expressed in Table 1. 1,2,5,[12][13][14][15][16][17][18] Data Extraction and Study Quality Assessment Two investigators (LAR, GP) independently extracted data and assessed the quality of the included studies as described below. The data extracted included study design, sample size, demographic details, and any of the aforementioned outcome variables.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%